2008
DOI: 10.1186/1476-4598-7-13
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I gene therapy reverses morphologic changes and reduces hyperprolactinemia in experimental rat prolactinomas

Abstract: Background: The implementation of gene therapy for the treatment of pituitary tumors emerges as a promising complement to surgery and may have distinct advantages over radiotherapy for this type of tumors. Up to now, suicide gene therapy has been the main experimental approach explored to treat experimental pituitary tumors. In the present study we assessed the effectiveness of insulin-like growth factor I (IGF-I) gene therapy for the treatment of estrogen-induced prolactinomas in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In a previous study we demonstrated that IGF-I gene therapy in estrogen-induced pituitary tumors partially reduced the marked hyperprolactinemia of the animals and also tended to reverse morphometric changes in the lactotrope population [Cónsole et al, 2008]. The present results extend our findings by showing that IGF-I gene therapy in estrogen-induced pituitary tumors is also beneficial for the somatrotropic cell population.…”
Section: Discussionsupporting
confidence: 76%
“…In a previous study we demonstrated that IGF-I gene therapy in estrogen-induced pituitary tumors partially reduced the marked hyperprolactinemia of the animals and also tended to reverse morphometric changes in the lactotrope population [Cónsole et al, 2008]. The present results extend our findings by showing that IGF-I gene therapy in estrogen-induced pituitary tumors is also beneficial for the somatrotropic cell population.…”
Section: Discussionsupporting
confidence: 76%
“…Bearing in mind the common embryological origin of lactotropic and somatotropic cells, we suggest that there is a possibility that chronic hyperprolactinemia may suppress GH secretion. On the other hand, there is some evidence that IGF-1 gene therapy reverses morphological changes and reduces hyperprolactinemia in rats with prolactinomas [20].…”
Section: Correlation Of Prolactin Levels and Variables Within The Stumentioning
confidence: 99%
“…Although important advances have been made in the treatment of pituitary tumors with surgery and radiotherapy as well as pharmacological approaches, a fully marked hyperprolactinemia of the animals and also tended to reverse phenotype changes in the lactotrope population [Cónsole et al, 2008]. The mechanism by which pituitary overexpression of IGF-I inhibits lactotropic cell growth and PRL secretion is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that in vivo delivery of the gene for rat IGF-I in estrogen-induced rat prolactinomas was able to partially reverse hyperprolactinemia and restore lactotrope [Cónsole et al, 2008] and somatotrope cell morphology . In the present study, we expanded our investigations into the actions of IGF-I gene therapy in estrogen-induced pituitary tumors by assessing the effect of this treatment on other endocrine pituitary cell populations in these tumors.…”
mentioning
confidence: 99%